Beyond Recidivism: An Outcome Evaluation of A Federal Reentry Court and A Critical Discussion of Outcomes that Matter. (2nd July 2020) - Taylor, Caitlin J.
Abstract: Relatively little empirical research has documented reentry courts' effectiveness. Even less scholarship has critically evaluated their varied goals. A quasi-experimental outcome evaluation of a federal reentry court reveals that the program increases access to social services, decreases probation revocations, and increases future employment. However, the program does not reduce the likelihood of new arrests. These findings are interpreted in the context of the collateral consequences of mass incarceration, a desistance from crime lens, and a human rights perspective.